Bahasa Melayu dan Jati Diri dalam Konteks Satu Malaysia: Satu Kupasan Linguistik (Jurnal Bahasa, 2010)
Every country has pride in its national identity. A major element of thisidentity is language and culture. Malaysia, originally known as TanahMelayu, has stipulated that the Malay language is the official nationallanguage as enshrined in its constituition. The status is well acceptedand become the medium of instruction in the education system inconsistence with the Razak Report (1956). However, innovations ineducation system in the post-Razak era have weakened the position ofthe Malay language. The new policy emphasising on the importanceof science and technology and the English language has resulted ina loss of confidence in the Malay Language among some parts of thepopulation. This development is parallel with the new world orderand language imperialism which stress the importance of English andthus undermined the national language. Nor Hashimah et al. (2009)shows that there is a correlation between the poor command of theMalay language among teenagers and the weakening of the Malaylanguage sovereignty. This article attempts to analyze the status ofthe Malay language today in the context of One Malaysia from thelinguistic perspective.Keywords: terminology, linguistic imperialism, neo imperialism,hegemony power, national identity